PEREMPUAN DAN BIMBINGAN KEAGAMAAN PADA KOMUNITAS MAJLIS TAKLIM AS–SALAM - Abdul Aziz; Lukman Nulhakim (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to see how the process of religious guidance is carried out by women in the As-Salam As-Salam Assembly community in Sentebang Village to its members. Women also have a position to contribute to guiding and directing members of the taklim assembly to understand the values of Islamic teachings as a way of life for them. This research was conducted in a qualitative descriptive manner with interviews and analysis as a method for collecting data during the research process. The conclusion of this study is the role of women in the as-salam taklim assembly community to direct, guide individuals to always walk according to Islamic religious law. The guidance method used is in the form of individual guidance and group guidance which is carried out regularly by the as-salam taklim assembly community